(untitled) (Teacher Education through Flexible Learning in Africa (TETFLE), 2023)
ABSTRACT To ensure that all students studying through the open and distance learning (ODL) system have enduring learning experience and success, there is a need for a practical and effective student support system. Research in the United Kingdom and elsewhere has shown that the rate of attrition is higher in ODL when compared to the conventional systems. In an ODL environment, student support services entail academic, psychosocial, and administrative support. Botswana Open University (BOU) is no exception to having pitfalls considering the queries raised by students. This study assessed the effectiveness of student support services in an ODL institution like BOU. The researchers adopted Tinto’s Student Integration Model as their theoretical benchmark. The model states that students are more likely to remain enrolled in an institution if they become connected to the social and academic life of that institution. A qualitative design involving interviewing tutors, students, heads of departments, tutor coordinators, and the student counsellor allowed for collection of data that was thematically analysed. The findings identified challenges related to administrative, academic and psychosocial support. Based on these findings, recommendations were made to improve student support services at BOU. Key words: Student Support Services, Open and Distance Learning, eLearning Support, Academic support, Psychosocial support, administrative support